Lung function response and side effects to rapamycin for lymphangioleiomyomatosis: a prospective national cohort study. Issue 4 (9th October 2017) - Bee, Janet; Fuller, Sharon; Miller, Suzanne; Johnson, Simon R
Abstract : Rationale: Mechanistic target of rapamycin inhibitors reduce loss of lung function in lymphangioleiomyomatosis (LAM), although their benefit varies between individuals. We examined lung function response and side effects to rapamycin in a national cohort. Methods: Subjects were receiving rapamycin for progressive lung disease. Clinical evaluation, detailed phenotyping, serial lung function, rapamycin and safety monitoring were performed according to a clinical protocol. Lung function change, measured as FEV1 slope (ΔFEV1 ), was reported for those treated for 1 year or longer. Results: Rapamycin was associated with improved ΔFEV1 in 21 individuals where pretreatment data were available (p<0.0001). In 47 treated for a mean duration of 35.8 months, mean ΔFEV1 was +11 (SD 75) mL/year, although it varied from +254 to −148 mL/year. The quartile with the highest positive ΔFEV1 had greater pretreatment FEV1 (p=0.02) and shorter disease durations (p=0.02) than the lowest quartile. Serum rapamycin level was positively associated with side effects (p=0.02) but not ΔFEV1 over 1 year. Within the first month of therapy, apthous ulcers, nausea and diarrhoea were associated with higher rapamycin levels. Acne, oedema and menstrual irregularities tended to increase over the first year of therapy. At the end of observation, the prevalence of side effects was 5% or less. Conclusions: Rapamycin reduces lung function loss in LAM, although in some, ΔFEV1 continues to fall at an accelerated rate. Poor response to rapamycin was associated with lower pretreatment lung function and longer disease duration but not serum level. Early intervention with low-dose rapamycin may preserve lung function and reduce side effects.